PARADIGM-2: Two parallel phase I studies of olaparib and radiotherapy or olaparib and radiotherapy plus temozolomide in patients with newly diagnosed glioblastoma, with treatment stratified by MGMT status. (January 2018) - Fulton, Ben; Short, Susan C.; James, Allan; Nowicki, Stefan; McBain, Catherine; Jefferies, Sarah; Kelly, Caroline; Stobo, Jon; Morris, Anna; Williamson, Aoife; Chalmers, Anthony J.
Highlights: The manuscript details the rationale, design and protocol for PARADIGM-2. PARADIGM-2 comprises two parallel phase I, dose escalation studies of the PARP inhibitor olaparib in combination with radiotherapy (for MGMT unmethylated patients) and radiotherapy-temozolomide (for MGMT methylated patients) in newly diagnosed glioblastoma. This is a novel approach to phase I dose escalation trial design that maximises the potential for patients with glioblastoma to benefit from the addition of the radio- and chemosensitizing drug olaparib. Abstract: Glioblastoma has a dismal prognosis and molecular targeted agents have failed to improve outcomes to date. PARADIGM-2 is a phase I dose escalation study evaluating olaparib plus radiotherapy ± temozolomide in newly diagnosed glioblastoma, using MGMT methylation status to stratify patients and inform treatment schedules.